Asiatic acid inhibits lung cancer cell growth in vitro and in vivo by destroying mitochondria - Wu, Tiancong (Acta Pharm Sin B, 2017)
Asiatic acid (AA), a pentacyclic triterpene found in Centella asiatica, displays significant anti-proliferative effects on cancer cells in vitro although the underlying mechanism of this effect remains unknown. This study investigated the efficacy and mechanism of action of AA against lung cancer both in vivo and in vitro. Using the MTT assay, AA was found to induce apoptosis in a dose- and time-dependent manner, an effect enhanced by pretreatment with an autophagy inhibitor. It also elevated expression of microtubule-associated protein 1 light chain 3 (LC3) and decreased the expression of p62. Furthermore, exposure to AA resulted in collapse of the mitochondrial membrane potential and generation of reactive oxygen species (ROS), suggesting mitochondria are the target of AA. In the mouse lung cancer xenograft model, oral administration of AA significantly inhibited tumor volume and weight accompanied by significant apoptosis of lung cancer cells. In addition, it led to a significant decrease in the expression of proliferating cell nuclear antigen (PCNA). In summary, the results show that AA significantly reduces lung cancer cell growth both in vitro and in vivo and that the associated apoptosis is mediated through mitochondrial damage.